A User-Level Scheduling Framework for BoT Applications on Private Clouds - Santos, Maicon Ança dos; Du Bois, André Rauber; Cavalheiro, Gerson Geraldo Homrich (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2017: Anais do XXIX International Symposium on Computer Architecture and High Performance Computing, 2017)
This paper presents a high level model to describe bag of tasks (BoT) applications and a framework to evaluate user level approaches to scheduler BoTs on coarser works units. The scheduler consolidates the load of the tasks in a given number of virtual machines (VMs) providing the estimated makespan. The framework allows to change the policy of tasks selection in order to compare the length of the scheduling produced giving a limited number of VMs. The framework has as input a BoT description and produces for each VM its trace of processing load. This paper validates the BoT model and the proposed framework with a performance assessment. In our case studies, the output of the framework is submitted to a real OpenStack based IaaS infrastructure. The results show that the makespan can be reduced by grouping tasks in coarse units of loads.